Systematic Review of Safety and Efficacy of Rituximab in Treating Immune-Mediated Disorders - Kaegi, Celine; Wuest, Benjamin; Schreiner, Jens; Steiner, Urs C.; Vultaggio, Alessandra; Matucci, Andrea; Crowley, Catherine; Boyman, Onur (Frontiers in Immunology, 2019)
Background: During the past years biologic agents (also termed biologicals or biologics) have become a crucial treatment option in immunological diseases. Numerous articles have been published on biologicals, which complicates the decision making process on the use of the most appropriate biologic for a given immune-mediated disease. This systematic review is the first of a series of articles assessing the safety and efficacy of B cell-targeting biologics for the treatment of immune-mediated diseases. Objective: To evaluate rituximab's safety and efficacy for the treatment of immune-mediated disorders compared to placebo, conventional treatment or other biologics. Methods: The PRISMA checklist guided the reporting of the data. We searched the PubMed database between 4 October 2016 and 26 July 2018 concentrating on immune-mediated disorders. Results: The literature search identified 19’665 articles. After screening titles and abstracts against the inclusion and exclusion criteria and assessing full texts, 105 articles were finally included in a narrative synthesis. Conclusions: Rituximab is both safe and effective for the treatment of acquired angioedema with C1-inhibitor deficiency, ANCA-associated vasculitis, autoimmune hemolytic anemia, Behçet’s disease, bullous pemphigoid, Castleman’s disease, cryoglobulinemia, Goodpasture’s disease, IgG4-related disease, immune thrombocytopenia, juvenile idiopathic arthritis, membraneous nephropathy, relapsing-remitting multiple sclerosis, myasthenia gravis, nephrotic syndrome, neuromyelitis optica, pemphigus, rheumatoid arthritis, spondyloarthropathy, and systemic sclerosis. Conversely, rituximab failed to show an effect for antiphospholipid syndrome, autoimmune hepatitis, IgA nephropathy, inflammatory myositis, primary progressive multiple sclerosis, systemic lupus erythematosus, and ulcerative colitis. Finally, mixed results were reported for primary Sjögren’s syndrome and Graves’ disease, therefore warranting better quality trials with larger patient numbers.